Intrapersonal conflict between christianity and homosexuality: the personal effects faced by gay men and lesbians. - Subhi, N.,; Mohamad, S. M,; Sarnon, N,; Nen, S.,; Hoesni, S.M,; Khadijah Alavi,; Chong, Sheau Tsuey (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
Potential conflict between Christianity and homosexuality is not considered as a totally new phenomenon.Nonetheless, since scarce is known regarding the matter this might assumed the level of intolerance is still high within most traditional western religion including Christianity. A qualitative study of 10 male and 10 female Christian homosexuals was conducted via in-depth semi-structured interviews. This paper seeks to explore the potential conflict between Christianity and homosexuality faced by the respondents. The result found that the majority, eighty percent (80%), were affected by the conflict, suggesting that both Christianity and homosexuality were important components of their lives. The most common personal effects of conflict between Christianity and homosexuality indentified included depression (68.8%), selfblame/guilt (37.5%), anxiety (31.3%), suicidal ideation (25%) and alienation (25%). Implications and recommendations at three levels are provided to assist those dealing with homosexual people who are affected by the conflict.